Molecular mechanism of central nervous system repair by the Drosophila NG2 homologue kon-tiki. - Losada-Perez, M.; Harrison, N.; Hidalgo, A. (Journal of Cell Biology, 2016)
Neuron glia antigen 2 (NG2)-positive glia are repair cells that proliferate upon central nervous system (CNS) damage, promoting functional recovery. However, repair is limited because of the failure of the newly produced glial cells to differentiate. It is a key goal to discover how to regulate NG2 to enable glial proliferation and differentiation conducive to repair. Drosophila has an NG2 homologue called kon-tiki (kon), of unknown CNS function. We show that kon promotes repair and identify the underlying mechanism. Crush injury up-regulates kon expression downstream of Notch. Kon in turn induces glial proliferation and initiates glial differentiation by activating glial genes and prospero (pros). Two negative feedback loops with Notch and Pros allow Kon to drive the homeostatic regulation required for repair. By modulating Kon levels in glia, we could prevent or promote CNS repair. Thus, the functional links between Kon, Notch, and Pros are essential for, and can drive, repair. Analogous mechanisms could promote CNS repair in mammals.